Experimental investigation on suppression of thermal runaway propagation of lithium-ion battery by intermittent spray. (February 2023) - Zhang, Lin; Duan, Qiangling; Xu, Jiajia; Meng, Xiangdong; Sun, Jinhua; Wang, Qingsong
Abstract: Thermal runaway (TR) initiated in an individual cell may cause TR propagation in lithium-ion battery (LIB) module, and the likelihood increases due to the higher energy density and poor heat dissipation. Therefore, the suppression of TR propagation is critical to protecting battery safety. This work investigated a TR propagation suppression strategy using intermittent spray. To comprehensively understand the suppression mechanisms, the extinguishing, cooling, and suppression capabilities were discussed by changing the duty cycles (DC) and periods (Pt ) of intermittent spray. Experimental results show that TR propagated rapidly from failed cells to the LIB module without effective suppression measures, and TR propagation interval is the optimum suppression stage, thereby timely and effective suppression measures can mitigate or even prevent TR propagation. However, the suppression capability is not only related to the total heat dissipation, but also the cooling power during the suppression stage. When the average cooling power is sufficient to mitigate TR propagation, the cooling capability dominates the control process, which decreases with the increasing period, and initially increases and then declines with the decrease of duty cycle. Moreover, in this work, an intermittent spray (Pt = 2 s, DC = 0.5) possesses better extinguishing and suppression capabilities, while another intermittent spray mode (Pt = 20 s, DC = 0.25) shows higher water utilization and better cooling effect. Based on this finding, a novel TR propagation suppression strategy combining these two intermittent spray modes can quickly extinguish the fire, accelerate the cooling process and finally prevent TR propagation. Highlights: The thermal runaway (TR) propagation characteristics in LIB array are studied. The TR propagation suppression mechanism of intermittent spray is discussed. Both the period and duty cycle of intermittent spray affect the suppression effect. An optimal suppression strategy is proposed to suppress TR propagation.